Clinical evaluation of a self-adhering flowable composite as occlusal restorative material in primary molars: one-year results - Muharrem Cem Doğan; Ceren Deveci̇; İ̇ffet Yazıcıoğlu; Buse Ayşe Seri̇n (Istanbul University, 2019)
Purpose: The aim of this study was to evaluate and compare the 1 year clinical performances of a self-adhering flowable composite and a commercially available self-etch adhesive/composite system in occlusal restorations of primary second molars. Patients and Methods: Thirty-one patients (10 male, 21 female) were recruited into the study. A total of 62 occlusal cavities were restored with either a universal composite or a self-adhering flowable composite according to manufacturers' instructions. The restorations were clinically evaluated 1 month after placement as baseline, and after 3, 6 months and 1 year post-operatively using modified USPHS criteria by two operators. Results: Lack of retention was not observed in any of the restorations. With respect to color match, marginal adaptation, secondary caries and surface texture, no significant differences were found between two restorative materials tested after 1 year. None of the restorations had marginal discoloration and anatomic form loss on the 1 year follow-up. Restorations did not exhibit post-operative sensitivity at any evaluation period. Conclusion: The clinical assessment of self-adhering flowable composite exhibited good clinical results with predominating alpha scores after 1 year. Advantage of the application convenience for children is promising for self-adhered flowable composite materials in pediatric use.